Multimedia Interaktif untuk Mengatasi Problematika Pembelajaran Bahasa Arab - Aulia Mustika Ilmiani; Ahmadi Ahmadi; Nur Fuadi Rahman; Yulia Rahmah (Universitas Islam Negeri Palangka Raya, 2020)
The use of media, especially in learning Arabic in Indonesia has been proven to be significant. Many studies prioritize the use of certain media in the learning process so that it can overcome the problems of learning Arabic. This descriptive qualitative study discusses the use of interactive multimedia in learning Arabic at IAIN Palangka Raya. This study aims to explore interactive multimedia used by PBA lecturers to overcome the problems of learning Arabic. Data collection techniques used are observation, interviews and documentation. The results of the study are: first, in terms of time and place of implementation, namely IAIN Palangka Raya e-learning, Arabic online and Bahasaarab312.gnomio.com. Second, viewed from the materials being taught, multimedia PowerPoint was used which included cartoon story maker media, Arabic Online, camtasia, active presenter, e-book learning, YouTube, kine master, pollagon, Arabee. Third, seen from the needs of students, Macromedia / Adobe Flash was relevant. The Arabic learning problems that can be overcome with the use of interactive multimedia are as follows. 1) In terms of linguistics, using interactive multimedia, lecturers become easier in demonstrating teaching or learning materials to 2) in terms of practical (non-linguistic) using multimedia interactive, PBA lecturers can attract the students ‘interests and attention who lack of motivation in learning Arabic.